New Research on Detection and Removal of Emerging Pollutants (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This is the reprint of the Topic on “New Research on the Detection and Removal of Emerging Pollutants”. The journals involved in the SI were Materials, Processes, Sustainability, Applied Sciences, and Toxics, contributing 23, 21, 13, 7, and 2 interesting and high-quality papers, respectively, to the broad field of research on emerging pollutants. The removal of emerging pollutants is a challenging topic receiving increasing attention in terms of investigations and the risk concerns perceived by society. In fact, improving the means for both the quantification and removal of toxic substances is clearly relevant in the current situation of environmental stress affecting different environmental compartments. Combining the five journals mentioned above in this one Topic has promoted a wider diffusion of the issue, covering a wide spectrum of researchers and readers. This field needs continuous higher efforts, so it is expected that additional related SIs and Topics will be developed in the future.